Drying Shrinkage Strain Development of Agro-Waste Oil Palm Shell Lightweight Aggregate Concrete by Using the Experimental Result, ACI and Eurocode Prediction Models - Maghfouri, Mehdi (International Journal of Integrated Engineering, 2019)
Oil palm shell (OPS) is a waste from the agricultural sector in tropical regions which could be used as aggregate in lightweight concrete mixtures. Different types of lightweight concrete with satisfactory mechanical properties were produced by using OPS. However, at early and later ages, oil palm shell lightweight aggregate concrete has higher rate of drying shrinkage compare to the normal-weight concrete. The aim of the present study is to compare the development of drying shrinkage strain based on the prediction models and experimental results. In this regard, two concrete mixes using a different level of OPS as replacement of crushed granite were produced. Two prediction models, ACI-209R and Eurocode (EC2), were applied to estimate drying shrinkage strain. In order to obtain accurate prediction for drying shrinkage strain, all effective factors for the models were applied. From the test results for drying shrinkage strain, it could be reported that both ACI and EC2 models presented close results to the experimental curves for conventional concrete (C1 mix). While, due to the high substitution level of OPS (up to 100% of aggregates) in conventional concrete, sharp increase in the drying shrinkage was observed in C2 mix. Therefore, no any suitable prediction model was found to predict close results for such concretes at early and long-term ages. Furthermore